2001
DOI: 10.1046/j.1365-2303.2001.00375.x
|View full text |Cite
|
Sign up to set email alerts
|

Personal view. Is it reality or an illusion that liquid‐based cytology is better than conventional cervical smears?

Abstract: Liquid-based cytology (LBC) has been heralded as the way forward for cervical screening, and as the answer to many of its problems. It is already used as a sole method of cell preparation in many private clinics in the UK. It is being used for colposcopy smears in many NHS clinics and is now being piloted for primary screening in three screening centres in England, as well as one in Scotland and one in Wales. LBC has been welcomed as a new technology because it deals with the problem of specimen adequacy at so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 17 publications
1
16
1
3
Order By: Relevance
“…Since the smear-taker was not responsible for slide preparation or fixation, slides were unlikely to be assessed as inadequate, equivocal or borderline because of poor fixation. 19 The inadequate rate in this study (5%) was high compared to most other reports. The majority (65%) were due to bleeding, with the rest being either hypocellular or acellular.…”
Section: Cytologycontrasting
confidence: 59%
“…Since the smear-taker was not responsible for slide preparation or fixation, slides were unlikely to be assessed as inadequate, equivocal or borderline because of poor fixation. 19 The inadequate rate in this study (5%) was high compared to most other reports. The majority (65%) were due to bleeding, with the rest being either hypocellular or acellular.…”
Section: Cytologycontrasting
confidence: 59%
“…There are some concerns that liquid based cytology might falsely label inadequate smears as negative, and such an adverse effect would take several years to become evident in a programme with a three to five year screening interval. 12 Health technology assessment reports from New Zealand and Australia also concluded that the introduction of liquid based cytology was not justified by current evidence. 14 15 Thus, the problem of "inadequate cervical smear" will probably stay with us for some time, and it is important to understanding fully its clinical and prognostic significance.…”
Section: Discussionmentioning
confidence: 99%
“…11 This may be a result of the different criteria used by the NHSCSP, and may also reflect the longer screening interval in the UK. 12 The NHSCSP recognises inadequate smears as a major problem, being one of the main reasons for piloting liquid based cytology for primary screening in England and Wales. The clinical and prognostic significance of inadequate cervical smears is uncertain, and the NHSCSP guidance requiring women with repeated inadequate cervical smears to be referred for colposcopy has been questioned.…”
Section: Discussionmentioning
confidence: 99%
“…[22] To our knowledge, this is the first reported case of a primary thyroid carcinoma confirmed by LBC. Although cervical smear using LBC preparation has been described, [23] the role of LBC in thyroid aspiration cytology has yet to be explored. We expect the clinical application of LBC in thyroid fine needle aspiration cytology to help in establishing correct preoperative diagnoses.…”
Section: Bodymentioning
confidence: 99%